Do different sit–stand workstations influence lumbar kinematics, lumbar muscle activity and musculoskeletal pain in office workers? A secondary analysis of a randomized controlled trial. Issue 1 (2nd January 2022) - Brown, Whitney; Pappas, Evangelos; Foley, Bridget; Zadro, Joshua R.; Edwards, Kate; Mackey, Martin; Shirley, Debra; Voukelatos, Alexander; Stamatakis, Emmanuel
Abstract : Purpose. This study investigated the effect of different sit–stand workstations on lumbar spine kinematics, lumbar muscle activity and musculoskeletal pain. Methods. Thirty-two office workers were randomized to one of three sit–stand workstations (Group 1, ratio of minutes spent sitting to standing each hour at work 40:20, n  = 8; Group 2, 30:30, n  = 6; Group 3, 20:40, n  = 7) and a control group (usual sitting, n  = 11). Intervention groups (Groups 1, 2 and 3) were collapsed into one group for analysis ( n  = 21). Data on lumbar kinematics and muscle activity were only collected for 25 participants due to equipment availability. Results. Participants in the intervention group had lower overall lumbar spine flexion angles during the workday compared to the control group (mean difference 10.6°; 95% confidence interval [−18.1, −3.2]; p  = 0.008; Cohen's d  = 1.5). There were no between-group differences for the remaining kinematic measures (i.e., mean flexion angle in standing and sitting, mean side flexion angle in standing and sitting, and percentage of time in upright sitting), muscle activity or presence of musculoskeletal pain. Conclusions. Sit–stand workstations reduced overall lumbar spine flexion angles over the course of a workday but had no effect on other kinematic measures, lumbar spine muscle activity or musculoskeletal pain. Trial registration: Australian New Zealand Clinical Trials Registry identifier: ACTRN12615001018505. .